The Analysis of Relationship Between Learning Motivation And Student Procrastination Behavior in Public Elementary School - Faisal Kemal; Wa Ode Riniati; Aceng Haetami; Abdul Wahab; Emy Yunita Rahma Pratiwi (Departement of Mathematics Education, 2023)
This study aims to prove that there is a relationship between learning motivation and students' academic procrastination behavior at one of the Public Elementary School in Sukabumi, West Java. The research method used in this study is a quantitative method. The population is a group of elements or cases, be it individuals, objects or events, which are related to specific criteria and are something that becomes the target of generalizations set by the researcher to study and draw conclusions. The population in this study were all fifth grade elementary school students with a total of 64 students, consisting of 41 male students and 23 female students. Independent variables, namely variables that can influence or influence other variables and are denoted by the variable X. Based on the research results obtained through the process of data analysis and discussion, it can be concluded that there is a negative and significant relationship between learning motivation and students' academic procrastination with an r count of -0.539 and is in the category of moderate relationship level. The existence of a negative relationship means that if student learning motivation is high then student academic procrastination is low, and vice versa if student learning motivation is low then student academic procrastination is high.